Analisis Pengaruh Kebijakan Dividen, Book Value Per Share (Bvps), Dan Earning Volatility (Evol) Terhadap Volatilitas Harga Saham (Study Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Citra Damayani Prayogiyanto; Ronny Malavia Mardani; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract  The purpose of this study is to analyze the effect of Dividend Policy (DPR), Book Value Per Share (BVPS), and Earning Volatility (EVOL) on Stock Price Volatility (PVOL). The population used in this study was manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2016 - 2018. The sample used in this study was purposing sampling. Companies that fall into the study criteria consist of 35 companies for 3 years. The method used in this study is documentation of financial statements from manufacturing companies in the basic and chemical industry sectors listed on the IDX. The analysis used is multiple linear regression by testing the hypothesis using the t test. The results of this study explain that the dividend pay out ratio (DPR) has a positive effect on stock price volatility, book value per share (BVPS) has a positive effect on stock price volatility, earning volatility (EVOL) has a positive effect on stock price volatility.Keywords: Dividend Policy (DPR), Book Value Per Share (BVPS), Earning Volatility (EVOL), Stock Price Volatility (PVOL).